Anti-Lipoarabinomannan-Specific Salivary IgA as Prognostic Marker for Leprosy Reactions in Patients and Cellular Immunity in Contacts - Nahas, André Alan; Lima, Mayara Ingrid de Sousa; Goulart, Isabela Maria Bernardes; Goulart, Luiz Ricardo (Frontiers in Immunology, 2018)
Leprosy causes the most common peripheral neuropathy of infectious etiology, posing an important public health problem worldwide. Understanding the molecular and immunological mechanisms of nerve damage induced by M. leprae is mandatory to develop tools for early diagnosis and preventive measures. The phenolic glycolipid 1 (PGL-1) and lipoarabinomannan (LAM) antigens are major components of the bacterial surface and are implicated on leprosy immunopathogenesis and neural damage. Although the anti-PGL-1 serum IgM is highly used for operational classification of patients, the anti-LAM salivary IgA (sIgA) has not been investigated as diagnostic or prognostic marker in leprosy. Our aim was to assess the presence of anti-LAM sIgA in leprosy patients and their contacts in order to demonstrate whether such expression was associated with leprosy reactions. Distinct patterns of anti-LAM slgA were observed among groups, which were stratified into treatment-naïve patients (116), patients who completed multidrug therapy—MDT (39), household contacts (111), and endemic controls (11). Both anti-LAM sIgA and anti-PGL-I serum IgM presented similar prognostic odds toward leprosy reactions [(odds ratio) OR = 2.33 and 2.78, respectively]. Furthermore, the anti-LAM sIgA was highly correlated with multibacillary (MB) forms (OR = 4.15). Contrarily, among contacts the positive anti-LAM sIgA was highly correlated with those with positive Mitsuda test, suggesting that the presence of anti-LAM slgA may act as an indicator of cellular immunity conferred to contacts. Our data suggest that anti-LAM slgA may be used as a tool to monitor patients undergoing treatment to predict reactional episodes and may also be used in contacts to evaluate their cellular immunity without the need of Mitsuda tests.